A SYSTEM AND A DEVICE FOR ISOLATING CIRCULATING TUMOR CELLS FROM THE PERIPHERAL BLOOD IN VIVO - Michal Mego; Miroslav Kocifaj; František Kundracik (Acta Polytechnica, 2015)
Circulating tumor cells (CTC) play a crucial role in disseminating tumors and in the metastatic cascade. CTCs are found only in small numbers, and the limited amount of isolated CTCs makes it impossible to characterize them closely. This paper presents a proposal for a new system for isolating CTCs from the peripheral blood in vivo. The system enables CTCs to be isolated from the whole blood volume for further research and applications. The proposed system consists of magnetic nanoparticles covered by monoclonal antibodies against a common epithelial antigen, large supermagnets, which are used to control the position of the nanoparticles within the human body, and a special wire made of a magnetic core wrapped in a non-magnetic shell. The system could be used not only for isolating CTCs, but also for in vivo isolation of other rare cells from the peripheral blood, including hematopoietic and/or mesenchymal stem cells, with applications in regenerative medicine and/or in stem cell transplantation.